2-(2-Nitrophenyl)acetohydrazide - Praveen, A. S. (International Union of Crystallography, 2012)
In the title compound, C(8)H(9)N(3)O(3), the dihedral angle between the benzene ring and the acetohydrazide C—C(=O)—N—N plane [maximum deviation = 0.0471 (13) Å] is 87.62 (8)°. The nitro group is twisted by 19.3 (2)° with respect to the benzene ring. In the crystal, N—H⋯O hydrogen bonds link the molecules into a double-column structure along the b axis.